Estudo da rotatividade de pessoal no setor hoteleiro: impactos na aprendizagem e na qualidade - Taioli, Juliana Ayres (2005)
The duration of employer / employee relationships in an economy is an important factor in measuring the quality of employment and the efficiency of the country s productive system. The duration of employer/employee relationships in Brazil are considerably shorter in general than such relationships in Europe and the United States. Some sectors of the economy, particularly those centered around the services industry, are more sensitive to employment turnover. The tourism and hotel sector is an area where the rate of turnover is recognizably higher than average. As this is an area where a well-trained and qualified workforce is crucial for the well being of clients, it is important to study the causes of this high rate of turnover and evaluate the impacts it might be having on the quality of services rendered. This research examines the problem of turnover from the point of view of the human capital theory and evaluates its impact inside organizations. A case study on personnel turnover was done in a five-star hotel in the city of São Paulo, evaluating its impact on the quality of services. In the case studied, It was found that high turnover occurs mainly amongst individuals with higher education, probably overqualified for the positions they held. The research done shows no direct relationship between turnover and the quality of services rendered. However, as no evaluation was done on the individual performance of personnel, it is impossible to conclude whether the quality of services was directly influenced by this turnover or not. The theories of individual and organizational learning indicate that a high rate of turnover impairs the learning environment, which can jeopardize the strategic position of the company, as this affects the creation and transmission of tacit knowledge.